Supporting emergency remote teaching due to coronavirus pandemic: problem solving group at ICUDDR - Henriques, S.; Hopkins Eyles, C. (Aditktologie, 2021)
BACKGROUND: The COVID-19 pandemic has been challenging for all and has had a particular effect on university-level educators. Although the use of technologies in education is recognized as critical in developing transversal skills and preparing students for the needs of modern society, the COVID-19 pandemic crisis stressed the relevance of the digital medium. At the same time, the emergency hastened significant changes to universities’ main roles – teaching, learning, and evaluation. AIMS: In this article, we present research conducted by a Problem-Solving Group, a virtual community of practice formed by the International Consortium of Universities for Drug Demand Reduction (ICUDDR) to support educators in addressing the challenges of the pandemic crisis. METHODS: Based on a problem-solving methodology, the virtual community of practice Problem-Solving Group) provided synchronous group sessions and asynchronous individual support. The resulting analysis and discussion are based on the problem solving methodology. PARTICIPANTS: Twenty-two educators, including two facilitators, attended six virtual problem-solving sessions between September and December 2020. RESULTS: Participants were committed educators who shared their experiences, challenges, and best practices. The problem-solving methodology was effective in identifying critical areas in remote emergency university-level teaching. CONCLUSIONS: The results stress the importance of creating a common space where educators with similar problems and difficulties can share ideas, experiences, and best practices. The virtual community of practice was effective, although it requires more extensive development and research.